A novel accurate representation of a double-valued potential energy surface by the DMBE method. Application to triplet H3+(a3E') - Varandas, António J. C. (2005)
Standard single-valued double many-body expansion (DMBE) theory has been extended to allow an accurate representation of a double-valued potential energy surface. With this new theory, the degeneracy of the two sheets along the conical intersection line can be guaranteed by construction. The method has been applied to the lowest triplet state of H3+ (a3E') for which the lowest vibrational levels have also been calculated.